622 Long term prognostic impact of right ventricular dysfunction in patients with COVID-19. (8th December 2021) - Silverio, Angelo; Scudiero, Fernando; Di Maio, Marco; Russo, Vincenzo; Cancro, Francesco Paolo; Esposito, Luca; Sordillo, Martina; Muraca, Iacopo; Citro, Rodolfo; Parodi, Guido; Vecchione, Carmine; Galasso, Gennaro
Abstract: Aims: The characteristics and clinical course of hospitalized patients with Coronavirus disease 2019 (COVID-19) have been widely described, while long-term data are still poor. The aim of this study was to evaluate the long-term clinical outcome and its association with right ventricular (RV) dysfunction in hospitalized patients with COVID-19. Methods and results: This was a retrospective multicentre study of consecutive COVID-19 patients hospitalized at seven Italian Hospitals from 28 February to 20 April 2020. The study population was divided into two groups according to echocardiographic evidence of RV dysfunction defined by tricuspid annular plane systolic excursion (TAPSE) value <17 mm in accordance with the current guidelines. The primary study outcome was 1-year mortality. The study population consisted of 224 patients (mean age 69 ± 14, male sex 62%); RV dysfunction was diagnosed in 63 cases (28%). Patients with RV dysfunction were older (75 vs. 67 years, P < 0.001) and showed a higher prevalence of coronary artery disease (27% vs. 11%, P = 0.003), heart failure (5% vs. 22%; P < 0.001), chronic obstructive pulmonary disease (13% vs. 38%; P < 0.001), and chronic kidney disease (12% vs. 39%; P < 0.001). Left ventricular ejection fraction (LVEF) was significantly lower in patients with RV dysfunction that in those without (55% vs. 50%; P < 0.001). The rate of mortality at 1-year was significantly higher in patients with RV dysfunction as compared with those without (67% vs. 28%; P ≤ 0.001). After propensity score matching, patients with RV dysfunction showed a significantly lower long-term survival than patients without RV dysfunction (62% vs. 29%, P < 0.001). At multivariable Cox regression analysis, TAPSE, LVEF and acute respiratory distress syndrome during the hospitalization were independently associated with 1-year mortality (Table). Conclusions: RV dysfunction is a relatively common finding in hospitalized patients with COVID-19 and is independently associated with an higher risk of mortality at one-year follow-up.